Implementation of the Jigsaw Type Cooperative Learning Model on Improving Achievement and Learning Motivation of Muhammadiyah in Mu'allimin Madrasah Muhammadiyah Yogyakarta - Istiqlal Yul Fanani; Riyan Dwi Yulian Prakoso; Charmaine Bissessar; Milica Gligorovic (Al-Hijr: Journal of Adulearn World, 2022)
This research aims to determine the enhancement of students ' achievement and motivation after action, to know the difference in achievement and motivation to learn in the subjects of the youth through the cooperative learning model of the jigsaw type, describing the constraints of teachers in using the kind of unified learning model in Class 3 A Madrasah mu'allimin Muhammadiyah Yogyakarta. This research is a collaborative class of action research. The subject of the study was a Grade 3 student of A Madrasah Tsanawiyah mu'allimin Muhammadiyah Yogyakarta 2021/2022, with as many as 31 students. This research focuses on the achievement and motivation to learn the Kemuhammadiyahan after implementing a cooperative learning model. Data collection techniques using observation, documentation, and tests. The data analysis techniques in this study used quantitative and qualitative descriptive. Based on the research achievements and motivation in learning, Kemuhammadiyahan, through the application of a jigsaw type cooperative learning model, experienced a significant increase. Thus the jigsaw type cooperative learning model can be applied to Kemuhammadiyahan subjects.